2019
DOI: 10.1002/ijc.32818
|View full text |Cite
|
Sign up to set email alerts
|

High RIG‐I expression in ovarian cancer associates with an immune‐escape signature and poor clinical outcome

Abstract: Ovarian cancer (OC) is the most lethal gynecological malignancy, with platinum‐based chemotherapy remaining the mainstay for adjuvant treatment after surgery. The lack of indication for immunotherapy may at least in part result from the lack of suitable biomarkers allowing stratification of potentially responding patients. In this monocentric study of 141 cases with OC, we used real‐time quantitative PCR to assess the expression of retinoic acid‐inducible gene‐I (RIG‐I) in primary tumor and healthy ovarian con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 64 publications
(130 reference statements)
3
38
0
2
Order By: Relevance
“…The most likely reason for this result was a multicollinearity problem. With regard to this phenomenon, similar results were also found in numerous tumor studies (69)(70)(71). Next, the prediction power of each of the two lncRNAs was estimated on the basis of the ROC curve, and the results revealed that lnc-8996 and lnc-4265 had better diagnostic prediction power (AUC equals 0.867 and 0.815, respectively).…”
Section: Lnc-8996 Lnc-4265 Lnc-3108 Lnc-8461 Expression Expression Exsupporting
confidence: 77%
“…The most likely reason for this result was a multicollinearity problem. With regard to this phenomenon, similar results were also found in numerous tumor studies (69)(70)(71). Next, the prediction power of each of the two lncRNAs was estimated on the basis of the ROC curve, and the results revealed that lnc-8996 and lnc-4265 had better diagnostic prediction power (AUC equals 0.867 and 0.815, respectively).…”
Section: Lnc-8996 Lnc-4265 Lnc-3108 Lnc-8461 Expression Expression Exsupporting
confidence: 77%
“…Immunohistochemically, the expression of RIG-1 was found on the sarcolemma of muscle fibers in the perifascicular area and on single immune cells in both subgroups (anti-Mi-2 + , anti-TIF-1γ + ). DDX58/RIG-1 was shown to be directly involved in virus recognition and interferon production (47,(65)(66)(67). Nevertheless, it has been shown that increased RIG-1 expression may be involved in limiting innate immune response and supporting tumor growth (67).…”
Section: Discussionmentioning
confidence: 99%
“…Retinoic acid Inducible Gene 1 (RIG-I) is a cytosolic RNA receptor ubiquitously expressed in most human body cells and is known for its major role in antiviral immune defense by inducing pyroptosis. RIG-I is also expressed in cancer cells, acting pro-inflammatory by expressing INF I and other cytokines [ 130 ]. In preclinical models, systemically applied RIG-I agonists were able to inhibit tumor growth via induction of immunogenic cancer cell death [ 131 133 ].…”
Section: Future Io Treatment Strategiesmentioning
confidence: 99%